Design of Intelligent Construction System for Assembly Building Based on Improved IoT (Informatica, 2024)
Assembled construction can serve the purpose of saving resources, reducing costs and minimizing the impact on the environment. The construction process is essentially impossible without the support of advanced information technology. The study analyzes the functional requirements of an intelligent construction system for assembly buildings in four stages: design, production, transportation and installation based on the Internet of Things technology in order to realize the collaborative efforts of the stakeholders of assembly buildings. Additionally, by utilizing social network analysis and synergy theory, the study develops a dual-objective optimization model that thoroughly takes into account the synergistic influence between assembly construction services and service quality. The findings indicated that the system combines both efficiency and safety, and the genetic simulated annealing algorithm used to improve the Internet of Things assembly intelligent construction system has a service quality value of 4.52, a synergy value of 5.26, and an objective function value of 4.81, which are greater than that of the genetic algorithm and the simulated annealing algorithm. This intelligent construction system serves as a model for the development of intelligent construction systems for assembly buildings. It enables the realization of process data sharing, enabling data-driven business decision-making, increased productivity, and decreased management costs.